Odmienność celów współczesnych korporacji oraz rola menedżerów w dążeniu do ich osiągania - Skorb-Gała, Alina (Differences of goals of contemporary corporations and meaning of managers in goals create process, 2006)
The paper mentioned the main dylemats about goals of contemporary corporations. The article describe meaning of managers in goals create process and meaning o corporate governance system in this process.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 296-302